The Efficiency of Repeated Debulking Surgery for Recurrent Ovarian Cancer (Eurasian Medical Research Periodical, 2022)
to estimate the effectiveness of repeated debulking surgeries and identify factors that determine the survival of patients with combined treatment of ovarian cancer recurrence.